2013
DOI: 10.1016/j.ejvs.2013.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Mesenchymal Stem Cells Stabilize Already-formed Aortic Aneurysms More Efficiently than Vascular Smooth Muscle Cells in a Rat Model

Abstract: We have shown in this rat model of AAA that BM-MSCs exert a specialized function in arterial regeneration that transcends that of mature mesenchymal cells. Our observation identifies a population of cells easy to isolate and to expand for therapeutic interventions based on catheter-driven cell therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 24 publications
2
35
0
Order By: Relevance
“…It has been demonstrated that bone marrow mesenchymal stem cell and SMC transplantation can stabilize growing abdominal aortic aneurysms in rats 8,9 and promote healing of saccular venous pouch aneurysms in dogs. 19 In a rabbit model of elastaseinduced saccular aneurysms, endovascular seeding of bone marrow mesenchymal stem cells promoted thrombus organization and caused the aneurysm to shrink in size.…”
Section: Local Cell Therapy Heals Aneurysms With Degenerated/decellulmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that bone marrow mesenchymal stem cell and SMC transplantation can stabilize growing abdominal aortic aneurysms in rats 8,9 and promote healing of saccular venous pouch aneurysms in dogs. 19 In a rabbit model of elastaseinduced saccular aneurysms, endovascular seeding of bone marrow mesenchymal stem cells promoted thrombus organization and caused the aneurysm to shrink in size.…”
Section: Local Cell Therapy Heals Aneurysms With Degenerated/decellulmentioning
confidence: 99%
“…[5][6][7] Previously it has been shown in models of fusiform aortic aneurysms that restoration of the cell content of the aneurysm with local cell transplantation can reduce the progression of the aneurysm. 8,9 We investigated the hypothesis that loss of mural cells will promote degenerative remodeling of the saccular aneurysm wall in thrombosed aneurysms, and that this degenerative remodeling can be reduced or compensated by direct transplantation of smooth muscle cells (SMCs) into the luminal thrombus.…”
mentioning
confidence: 99%
“…We have previously shown that increasing endothelial progenitors 36 and mesenchymal stem cells 37 by local cell therapy is able to slow the progression of experimental AAAs. In our study, we did not address whether CXCR4 + cell levels were increased into the peripheral blood after chronic AMD treatment.…”
mentioning
confidence: 99%
“…34 Over the past decade, our laboratory has promoted cell [35][36][37] or gene 38 therapy to stop further AAA expansion, but these 2 approaches are hampered by technical difficulties and potential high cost for a frequent disease. To this regard, 1 major result of our study is that the blockade of CXCR4 by AMD3100 limits AAA formation in mice but also stabilizes already-formed AAAs in 2 experimental models.…”
mentioning
confidence: 99%
“…As an illustrative example, the xenograft rat model [6] has been investigated to study aneurysm evolution and expansion in the abdominal aorta. Thus, it has been proved that the injection of mesenchymal stem cells (MSCs) cultured in hydrogel based on hyaluronic acid (HA) can regenerate injured vascular tissue and particularly stabilize the AAA improving thereby the mechanical resistance of the weakened arterial wall [7][8][9]. In this context, authors [10] focused especially on the optimization of the hydrogel based on hyaluronic acid (HA) from a biological point of view through the investigation of the MSC differentiation potential, their phenotype and viability when encapsulated in a hydrogel.…”
Section: Introductionmentioning
confidence: 99%